The Influence of Using Smart Apps Creator on Science Learning Interest of Grade VIII Students of SMP Negeri 33 Makassar City - Nurasma, Nurasma; Nawir, Muhammad; Nurindah, Nurindah (Fakultas Tarbiyah Institut Agama Islam Negeri (IAIN) Bone, 2025)
This study aims to determine the effect of the use of Smart Apps Creator on the interest in learning science of grade VIII students of SMP Negeri 33 Makassar. This research is a type of quantitative research with a pre-experimental approach, and a one-shot case study research design. The subject of the study is 73 students in grade VIII of SMP Negeri 33 Makassar for the 2024/2025 academic year. The data collection technique used observation and questionnaires. The data analysis used is descriptive and inferential statistical analysis. The results showed that as many as 50.68% of students were in the criteria of interest, with the percentage in each indicator, namely 84.16% of students showing feelings of pleasure, 82.41% showing activeness in learning, 83.18% showing interest in learning, and 78.90% showing involvement in learning. The results of the hypothesis test showed that the t-calculated value of the t-table >, which was 3.009 > 1.994 so that Ha was accepted and Ho was rejected. Based on the findings of these results, it can be concluded that there is an influence of the use of Smart Apps Creator on the interest in learning science of grade VIII students of SMP Negeri 33 Makassar.